2020
DOI: 10.3389/fpsyg.2019.02983
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cognitive Training for School-Aged Children and Adolescents With Attention Deficit/Hyperactivity Disorder: A Systematic Review

Abstract: Problems with executive functions (EF) are hallmark characteristics of Attention Deficit/Hyperactivity Disorder (ADHD). Therefore, this review analyzed the efficacy of cognitive training for EF in reducing ADHD symptomatology and improving educational, interpersonal, and occupational outcomes in children and adolescents with this disorder. A systematic search, using a PICO (population/participant, intervention/indicator, comparator/control, outcome) framework was carried out. From 2008 to 2018, resorting to EB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 52 publications
0
46
0
Order By: Relevance
“…This feedback, along with other feature suggestions from the wider evidence synthesis community captured via GitHub issues, was incorporated and the first release version of the package was uploaded to CRAN in November 2019. The tool has been well received and is beginning to be cited in the evidence synthesis literature 16‐20 …”
Section: Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This feedback, along with other feature suggestions from the wider evidence synthesis community captured via GitHub issues, was incorporated and the first release version of the package was uploaded to CRAN in November 2019. The tool has been well received and is beginning to be cited in the evidence synthesis literature 16‐20 …”
Section: Developmentmentioning
confidence: 99%
“…The tool has been well received and is beginning to be cited in the evidence synthesis literature. [16][17][18][19][20]…”
Section: Developmentmentioning
confidence: 99%
“…Several studies have been conducted in recent years into the effectiveness of non-pharmacological treatments for ADHD ( Pelham and Fabiano, 2008 ; Sonuga-Barke et al, 2013 ; Richardson et al, 2015 ; Watson et al, 2015 ; Scionti et al, 2020 ; Shrestha et al, 2020 ; Veloso et al, 2020 ). These non-pharmacological strategies include behavior modification techniques and cognitive behavioral therapy ( Fabiano et al, 2009 ); cognitive training ( Tamm et al, 2010 ; Shuai et al, 2017 ); training in self-instruction and techniques to enhance the capacity to inhibit responses ( Meichenbaum and Goodman, 1971 ) including computer-based interventions ( Martinovic et al, 2016 ; Rossignoli-Palomeque et al, 2018 ), training in problem solving ( Bransford and Stein, 1993 ), neurofeedback ( Zuberer et al, 2018 ; Cueli et al, 2019 ), training in social skills ( Sheridan et al, 1996 ; Storebo et al, 2012 ), peer intervention ( Cordier et al, 2018 ), and training in organizational skills ( Langberg et al, 2008 ); and psycho-educational strategies and instruction of parents and teachers in cognitive behavioral techniques ( Miranda et al, 2002 ; Pelham and Fabiano, 2008 ; Montoya et al, 2011 ; Rimestad et al, 2019 ); within the multi-modal approach, of particular importance are interventions focused on producing changes in neuro-psychological functions ( Pistoia et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found positive results from training in basic cognitive processes, leading to general improvement in executive functions ( Johnstone et al, 2012 ; Dias and Seabra, 2016 ; Lambez et al, 2020 ; Veloso et al, 2020 ). Furthermore, studies show the benefit of combining training in executive functions with other therapeutic strategies such as training in self-instruction ( Meichenbaum and Goodman, 1971 ), modeling, and self-reinforcement (and other behavior modification techniques), for the improvement of sustained attention, selective attention, planning, social skills, academic performance, and the principal symptomology of ADHD ( Miranda et al, 2002 ; Arco Tirado et al, 2004 ; Pérez, 2007 ; Ramalho et al, 2011 ; Sun, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the training of cognitive functions, even during a short period of time, significantly affects brain networks involved in executive functions, specifically working memory, flexibility, or inhibition capabilities [13]. In subjects with ADHD, several studies have tested the effect of cognitive therapy but results were inconsistent; a recent meta-analysis that examined the efficacy of cognitive training on more specific executive functions in subjects with ADHD showed promising results [14]. By gathering the results of 22 studies in children with ADHD (age range: 3-12 years), the authors reported that cognitive training improved the domains of executive functions in children with ADHD but also led to positive and direct effects on ADHD symptoms, social skills, and academic performance.…”
Section: Introductionmentioning
confidence: 99%